2005
DOI: 10.1590/s1517-83822005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Action of nisin and high pH on growth of Staphylococcus aureus and Salmonella sp. in pure culture and in the meat of land crab (Ucides cordatus)

Abstract: The aim of this study was to evaluate the potential of nisin and high pH to inhibit the growth of Staphylococcus aureus and Salmonella sp. in broth culture and when inoculated into meat of land crab. In pure cultures, the growth of S. aureus was strongly inhibited by nisin and the growth of Salmonella sp. was inhibited by nisin-EDTA (20 mM). The inhibition of S. aureus lasted for eight hours and Salmonella sp. growth was inhibited throughout the experiment (24 h). The high pH (pH 10.0 and 11.0 with NaHCO3-NaOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Grisi and Gorlach-Lira (2005) used a nisin concentration close to that used in the present experiment and found that this bacteriocin was bacteriostatic up to 8 h for S. aureus growth in BHI broth. However, after the lag period, the multiplication rate was similar to that in the absence of nisin, which is the behavior also associated with resistant cells.…”
mentioning
confidence: 92%
“…Grisi and Gorlach-Lira (2005) used a nisin concentration close to that used in the present experiment and found that this bacteriocin was bacteriostatic up to 8 h for S. aureus growth in BHI broth. However, after the lag period, the multiplication rate was similar to that in the absence of nisin, which is the behavior also associated with resistant cells.…”
mentioning
confidence: 92%
“… 15 , 16 The effectiveness of bacteriocins is often dependent upon environmental factors such as pH and temperature, interaction with food components, precipitation, inactivation, or uneven distribution of bacteriocin in the food matrix, and food microbiota. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Phages are components of the natural microflora that are present throughout food production, from the farm to the retail outlet. 17 They are stable and recovered from soil, sewage, water, farm and processing plant effluents, feces, and retail foods. 17 , 18 The USFDA has approved a bacteriophage preparation made from six individually purified bacteriophages for use as an antimicrobial agent against L. monocytogenes on ready-to-eat meat and poultry products.…”
Section: Introductionmentioning
confidence: 99%
“…Nisin has been shown to be effective in controlling spoilage and pathogenic bacteria in many meat products (6, 7, 16,19,23,24,26,34,36). However nisin activity may be affected by many factors, such as concentration, the target microorganisms, interaction with food components, fat content and phosphate type, processing and storage conditions of food (5, 10, 35).…”
mentioning
confidence: 99%